2017
DOI: 10.1016/j.fertnstert.2017.03.011
|View full text |Cite
|
Sign up to set email alerts
|

In vitro fertilization with preimplantation genetic diagnosis for aneuploidies in advanced maternal age: a randomized, controlled study

Abstract: Preimplantation genetic diagnosis for aneuploidy screening is superior compared with controls not only in clinical outcome at the first ET but also in dramatically decreasing miscarriage rates and shortening the time to pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
208
2
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 314 publications
(230 citation statements)
references
References 37 publications
6
208
2
4
Order By: Relevance
“…The incidence of chromosome abnormalities varies from about 40% in fertile egg donors to 80% in patients 41 to 42 years old . The literature presents only one RCT in women aged 38 to 40 using CCS applied on day 3 embryos . This study confirmed the same results obtained in the good prognosis population also in AMA patients showing an increase in implantation rate using PGT‐A.…”
Section: Strengthssupporting
confidence: 81%
See 1 more Smart Citation
“…The incidence of chromosome abnormalities varies from about 40% in fertile egg donors to 80% in patients 41 to 42 years old . The literature presents only one RCT in women aged 38 to 40 using CCS applied on day 3 embryos . This study confirmed the same results obtained in the good prognosis population also in AMA patients showing an increase in implantation rate using PGT‐A.…”
Section: Strengthssupporting
confidence: 81%
“…In young and good prognosis patients, a decreased but not significant miscarriage rate was observed in the PGT‐A group compared to controls, a result also confirmed by a meta‐analysis . Only the RCT on AMA patients showed that PGT‐A was associated with a significantly lower miscarriage rate (2.7% vs 39.0%, P = 0.0007) (Figure ) . Therefore, only in older patients, PGT‐A might have the advantage of reducing dramatically the miscarriage rate, encouraging the use of PGT‐A in this population.…”
Section: Strengthsmentioning
confidence: 62%
“…The author is aware of one published randomized controlled trial, for older women aged 38 to 41 years, which has attempted to estimate cumulative outcome measures [18]. After excluding poor prognosis patients, the primary outcome measure was the delivery (live birth event) rate for the first transfer attempt, which should be expected to favour testing [7].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, with regard to their reason for wanting PGT‐A, significantly more patients who self‐assessed as knowing well or knowing a little about PGT‐A chose the “to give live birth” and not the “to avoid miscarriage” option. Indeed, several RCTs showed that PGT‐A improved the live birth rate and reduced miscarriage in a limited number of infertile patients with a favorable prognosis . However, in one study, PGT‐A did not improve the live birth rate or reduce the miscarriage rate in RPL patients .…”
Section: Discussionmentioning
confidence: 98%
“…However, there has been controversy regarding whether it can improve the live birth rate and prevent miscarriage in patients with RPL or aid infertile patients, although PGT‐A was originally developed in order to prevent miscarriage caused by aneuploidy at an advanced maternal age. With the progress made in scientific technologies such as array comparative genomic hybridization (aCGH), next generation sequencing (NGS) and trophectoderm biopsy, several randomized control trials (RCT) revealed that PGT‐A improved the live birth rate in limited populations with a favorable prognosis . However, several RCTs demonstrated no improvement in the live birth rate from its use .…”
Section: Introductionmentioning
confidence: 99%